Hitler's generals on trial: the last war crimes tribunal at Nuremberg - Hébert, Valerie (Modern war studies, 2010)
From war crimes to war crimes trials : the evolution of American judicial policy, 1942 to 1948 -- The response to the trials : attacks on all sides, 1946 to 1949 -- Prosecuting Hitler's high command : U.S. v. Wilhelm von Leeb, et al. -- The soldiers' defense -- Presiding Judge John Carlton Young and the high command case judgment -- The debate over imprisoned soldiers and the politics of punishment, 1949 to 1952 -- Setting the war criminals free : the interim and mixed clemency and parole boards, 1953 to 1958 -- Conclusion -- Appendix 1: The high command case -- Appendix 2: German Army field formations and basic command structure -- Appendix 3: Wartime positions of the high command case field commanders -- Appendix 4: The high command case defendants' sentence expiration and parole and clemency release dates